Sesquiterpenes and Sesquiterpene Derivatives from Ferula: Their Chemical Structures, Biosynthetic Pathways, and Biological Properties - Junchi Wang; Qi Zheng; Huaxiang Wang; Leiling Shi; Guoping Wang; Yaqin Zhao; Congzhao Fan; Jianyong Si (MDPI AG, 2023)
Ferula is a genus of flowering plants known for its edible and medicinal properties. Since ancient times, many species of Ferula have been used in traditional medicine to treat various health issues across countries, such as digestive disorders, respiratory problems, and even as a remedy for headaches and toothaches. In addition, they are also used as a flavoring agent in various cuisines. As the main active ingredients in Ferula, sesquiterpenes and their derivatives, especially sesquiterpene coumarins, sesquiterpene phenylpropanoids, and sesquiterpene chromones, have attracted the attention of scientists due to the diversity of their chemical structures, as well as their extensive and promising biological properties, such as antioxidative, anti-inflammatory, antibacterial properties. However, there has not been a comprehensive review of sesquiterpenes and their derivatives from this plant. This review aims to provide an overview of the chemical structures, biosynthetic pathways, and biological properties of sesquiterpenes and sesquiterpene derivatives from Ferula, which may help guide future research directions and possible application methods for this valuable edible and medicinal plant.